MathsGee is Zero-Rated (You do not need data to access) on: Telkom |Dimension Data | Rain | MWEB

1 like 0 dislike
101 views
Solve the equation $4(x - 1) + 2(2x - 3) - 2 = 15 - x + 3(3 - x)$
| 101 views

2 like 0 dislike

expand and collect like terms

$4x-4+4x-6-2=15-x+9-3x$

$8x+4x=15+9+12$

$12x=36$

$x=3$
by Diamond (45,616 points)
selected by
1 like 0 dislike
4x-4+4x-6-2=15-x+9-3x

12x=36

x=3
by Wooden (4,040 points)

0 like 0 dislike
1 like 0 dislike
0 like 0 dislike
2 like 0 dislike
0 like 0 dislike
1 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
1 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
1 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike